Meta-analysis on the effect of the N363S polymorphism of the glucocorticoid receptor gene (GRL) on human obesity - Marti, Amelia (BioMed Central, 2006)
BACKGROUND: Since both excess glucocorticoid secretion and central obesity are clinical features of some obese patients, it is worthwhile to study a possible association of glucocorticoid receptor gene (GRL) variants with obesity. Previous studies have linked the N363S variant of the GRL gene to increased glucocorticoid effects such as higher body fat, a lower lean-body mass and a larger insulin response to dexamethasone. However, contradictory findings have been also reported about the association between this variant and obesity phenotypes. Individual studies may lack statistical power which may result in disparate results. This limitation can be overcome using meta-analytic techniques. METHODS: We conducted a meta-analysis to assess the association between the N363S polymorphism of the GRL gene and obesity risk. In addition to published research, we included also our own unpublished data -three novel case-control studies- in the meta-analysis The new case-control studies were conducted in German and Spanish children, adolescents and adults (total number of subjects: 1,117). Genotype was assessed by PCR-RFLP (Tsp509I). The final formal meta-analysis included a total number of 5,909 individuals. RESULTS: The meta-analysis revealed a higher body mass index (BMI) with an overall estimation of +0.18 kg/m(2 )(95% CI: +0.004 to +0.35) for homo-/heterozygous carriers of the 363S allele of the GRL gene in comparison to non-carriers. Moreover, differences in pooled BMI were statistically significant and positive when considering one-group studies from the literature in which participants had a BMI below 27 kg/m(2 )(+ 0.41 kg/m(2 )[95% CI +0.17 to +0.66]), but the differences in BMI were negative when only our novel data from younger (aged under 45) and normal weight subjects were pooled together (-0.50 kg/m(2 )[95% CI -0.84 to -0.17]). The overall risk for obesity for homo-/heterozygous carriers of the 363S allele was not statistically significant in the meta-analysis (pooled OR = 1.02; 95% CI: 0.56–1.87). CONCLUSION: Although certain genotypic effects could be population-specific, we conclude that there is no compelling evidence that the N363S polymorphism of the GRL gene is associated with either average BMI or obesity risk.